2020
DOI: 10.3390/en13030756
|View full text |Cite
|
Sign up to set email alerts
|

Damage Evolution Mechanisms of Rock Induced by Blasting with the Aid of Empty-Hole Effect

Abstract: Blasting has been widely used in coal mining as a method of reducing the integrity of rock mass. Its low controllability often leads to the unsatisfactory fragmentation effect of rock mass. The empty borehole effect has great significance in avoiding the excessive breakage of rock mass and guiding the directional propagation of blasting-induced fractures. Nevertheless, the rock mass damage type evolution induced by the empty borehole has been rarely studied. A tension-compression constitutive model of rock mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…1). f 0 is the stress release rate of the rock mass surrounding the entry, which is 0.4 for elastic-plastic surrounding rock [43]; x is the distance between the EDWF and cross section A-A; and R A is the in uence radius of the EDWF, which is approximately equal to the excavation radius for this project (2.36 m). Fig.…”
Section: Stress Release Ratementioning
confidence: 99%
“…1). f 0 is the stress release rate of the rock mass surrounding the entry, which is 0.4 for elastic-plastic surrounding rock [43]; x is the distance between the EDWF and cross section A-A; and R A is the in uence radius of the EDWF, which is approximately equal to the excavation radius for this project (2.36 m). Fig.…”
Section: Stress Release Ratementioning
confidence: 99%
“…With the construction of large-scale intelligent mines, the double-roadway layout system will be chosen for more working faces. The research on controlling gob-side entry retaining roadways, gob-side entry driving roadways and rock surrounding the roadways has achieved many results, while there is less research on controlling of stability of the coal pillar and its supporting structures in the double-roadway layout system under the disturbance of roadway driving, working face mining, and repeated mining (Qi and Fourie, 2019;Zhang et al, 2020b;Meng et al, 2020;Chen et al, 2021a;Chen et al, 2021b). Wu et al (2019c) proposed the strengthening effect of high-intensity support and grouting on coal pillars in mining roadways.…”
Section: Introductionmentioning
confidence: 99%
“…In the process of rock fragmentation by parallel-hole cutting, existing empty holes provide new free faces, and the stress distribution around empty holes changes, leading to a stress concentration around empty holes that results in increased rock-breaking efficiency [21], which is known as an empty-hole effect during parallel-hole cutting [22]. Extensive research efforts have been performed in the empty-hole effect [23][24][25]. Li et al [26] identified the law of stress distribution during parallel-hole cutting using a numerical simulation method.…”
Section: Introductionmentioning
confidence: 99%